- Pengembangan Wawasan Kewirausahaan Berbasis Halal Knowledge di Desa Belapunranga Kec. Parangloe Kab. Gowa Provinsi Sulawesi Selatan: - - Nusran, Muhammad; Lantara, Dirgahayu; Muchlis, Nurmiati; Faisal AR Pelu, Muhammad (Window of Community Dedication Journal, 2021)
One of the main references for consumers in making requests for goods and services is to pay close attention to the halal label. In fact, only about 86% of MSME products in Indonesia are registered with halal certificates. Islamic boarding schools should be a place to socialize the importance of halal certification, as well as encourage entrepreneurship for students and the surrounding community. This, in fact, has not been in line with expectations, especially in remote areas. Educators do not yet have adequate scientific knowledge regarding halal certification procedures, as well as entrepreneurship. On the one hand, boarding school administrators are still required to meet operational costs to develop pesantren. On the other hand, many of the surrounding communities still have low socioeconomic status coupled with low education. This Community Partnership Program aims to solve problems in a comprehensive and sustainable manner through efforts to increase awareness and an entrepreneurial ethos based on "Halal Knowledge" in Remote Villages. The types of activities consist of Halal Product-Based Entrepreneurship Training, Halal Awareness Raising Training, Training Tips for Managing PIRT Permits and Halal Certification for Products to be Marketed and â€œJulehaâ€ (Halal Slaughter) and RPH (Slaughterhouse) Training. The implementation of the activity is carried out in three stages, namely the planning stage, the preparation stage and the implementation stage. After the activities are carried out, monitoring and evaluation activities are carried out to assess the effectiveness of the programs that have been implemented. Location The activity was carried out at the Muhammadiyah Hizbul Wathan Islamic Boarding School, Kasimburang Hamlet, Belapunranga Village, Gowa Regency. The conclusion obtained is that there is an increase in the knowledge and understanding of teachers, students and the surrounding community about the importance of halal products, increasing awareness and an entrepreneurial ethos based on "halal knowledge" in Kasimburang hamlet.